Seleksi Kemampuan Pematangan Oosit Domba Menggunakan Teknik Brilliant Cressyl Blue - Agus Setiadi, Mohamad; Supriatna, Iman (Jurnal Veteriner, 2010)
In present study the developmental competence of sheep oocytes to reach maturation at secondmetaphase (M II) was observed following selection of oocytes using brilliant cressyl blue (BCB).Immature oocytes were harvested from ovaries collected at abattoir; the selected according to theircolour appearence (cytoplasm colour) after being exposed to BCB and incubated for 90 minutes at5% CO2 incubator at 39oC. The selected oocytes were grouped into two based on their cytoplsmcolour i.e. group of oocytes (BCB+) with blue cytoplasm and growing oocytes (BCB-) the unstainedcytoplasm. The control group including freshly collected oocytes which were then selected usingroutine method by observing morphological character under microscope. Each treated group ofoocytes (BCB+ and BCB-) and the control were processed for maturation into culture media (TissueCulture Medium199+10 IU/ml Pregnant Mare Serum Gonadothropine+10 IU Human ChorionicGonadothropine+1?g/ml estradiol benzoat +10% fetal bovine serum) then incubated for 24 hours at5% CO2 incubator at 39oC. Finally oocytes from each treated group and the control were stainedwith arceto orcein 2% to observe the number of oocytes which reach maturatuion at M II. Theresult showed that the percentage of oocytes reaching M II were significantly higher in BCB+ group(54%) compared to BCB- group (8%). It is concluded that BCB is a potential method for selectionofcompetent oocytes
Keywords: Oocyte, sheep, competence, maturation